Acknowledging The Third Gender: Khunsa - Rahim, Rohani Abdul; Yaacob, Mohd Fadhly; Fandi, Fieza Fazlin (Universiti Sains Malaysia, 2016)
The terms Khuntha is not new in this era. It describe a human being who was born with natural differences in their sex anatomy and who’s biological cannot be classified either as a male or female. A Khuntha may have biologically attribution of both sexes or in some cases was lack in the biological attribution that makes it difficult to determine whether they are male or female. A Khuntha differs from a Transvestite or Transgender. Transvestite or Transgender are persons whom had deliberately alter their own anatomical character to the opposite. Currently a Khuntha faced challenges either in the society and/or in law. They are marginalized into an edge that had cause distress to their mentality as their privacy and right had been jeopardized. Many human right instruments only protect the right of male and female but failed to identify the right of a Khuntha. But even if their rights are explicitly stated in the law, it’s still difficult for a Khuntha to enforce those rights. A khuntha faced a lot of discrimination in all aspect of life and was subjected to homophobia.